2000
DOI: 10.1161/01.res.87.12.1172
|View full text |Cite
|
Sign up to set email alerts
|

The β 2 -Adrenergic Receptor Delivers an Antiapoptotic Signal to Cardiac Myocytes Through G i -Dependent Coupling to Phosphatidylinositol 3′-Kinase

Abstract: Recent studies have shown that chronic beta-adrenergic receptor (beta-AR) stimulation alters cardiac myocyte survival in a receptor subtype-specific manner. We examined the effect of selective beta(1)- and beta(2)-AR subtype stimulation on apoptosis induced by hypoxia or H(2)O(2) in rat neonatal cardiac myocytes. Although neither beta(1)- nor beta(2)-AR stimulation had any significant effect on the basal level of apoptosis, selective beta(2)-AR stimulation protected myocytes from apoptosis. beta(2)-AR stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
283
1
8

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(313 citation statements)
references
References 22 publications
13
283
1
8
Order By: Relevance
“…An increasing number of other studies have also reported that members of the GPCR superfamily activate PKB, including m1 and m2 muscarinic receptors, adenosine A 1 and A 3 receptors, b 2 and b 3 adrenoceptors and the CB 1 cannabinoid receptor (Murga et al, 1998;Gerhardt et al, 1999;Chesley et al, 2000;Germack & Dickenson, 2000;Go mez et al, 2000;Gao et al, 2001). It is interesting to note that b 2 and b 3 adrenoceptor-mediated activation of PKB was inhibited by pretreatment with pertussis toxin and PI-3K inhibitors.…”
Section: Discussionmentioning
confidence: 95%
“…An increasing number of other studies have also reported that members of the GPCR superfamily activate PKB, including m1 and m2 muscarinic receptors, adenosine A 1 and A 3 receptors, b 2 and b 3 adrenoceptors and the CB 1 cannabinoid receptor (Murga et al, 1998;Gerhardt et al, 1999;Chesley et al, 2000;Germack & Dickenson, 2000;Go mez et al, 2000;Gao et al, 2001). It is interesting to note that b 2 and b 3 adrenoceptor-mediated activation of PKB was inhibited by pretreatment with pertussis toxin and PI-3K inhibitors.…”
Section: Discussionmentioning
confidence: 95%
“…Our observations may also be extrapolated to other demyelinating diseases, such as multiple sclerosis, where demyelination could lead to the availability of myelin debris, transforming myelin-derived sulfatides into environmental toxins (31, 89 -91) that may impair remyelination. In this regard, other myelin components, such as myelin-associated glycoprotein, myelin oligodendrocyte glycoprotein, and Nogo A, are known to exert inhibitory functions, decreasing the regenerative capacity of the brain (92)(93)(94).…”
Section: Discussionmentioning
confidence: 99%
“…AChsensitive K ϩ (K ACh ) gives rise to an outward K ϩ current at membrane potentials corresponding to the AP plateau (43). In summary, there are at least three signaling pathways that can, therefore, account for the CCh-induced negative inotropy: 1) activation of the inwardly rectifying current I K ACh and APD shortening (20,54); 2) reduction in AC turnover and cAMP levels (18); and 3) activation of PI3K activity to reduce I CaL (10).…”
Section: Discussionmentioning
confidence: 99%